2022
DOI: 10.3390/app122211743
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the Application of Artificial Intelligence Techniques to the Management of Innovation Projects

Abstract: Due to their specific characteristics, innovation projects are developed in contexts with great volatility, uncertainty, complexity, and even ambiguity. Project management has needed to adopt changes to ensure success in this type of project. Artificial intelligence (AI) techniques are being used in these changing environments to increase productivity. This work collected and analyzed those areas of technological innovation project management, such as risk management, costs, and deadlines, in which the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Similarly, in [26], the results demonstrate that ML is highly beneficial for construction PM due to its capacity to enhance planning, measurement, performance, and decision-making. In [27], it is demonstrated that AI has a positive impact on risk management, cost efficiency, and time efficiency. It also enhances productivity by overcoming barriers caused by project variability, uncertainty, and complexity.…”
Section: Review Of Relatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in [26], the results demonstrate that ML is highly beneficial for construction PM due to its capacity to enhance planning, measurement, performance, and decision-making. In [27], it is demonstrated that AI has a positive impact on risk management, cost efficiency, and time efficiency. It also enhances productivity by overcoming barriers caused by project variability, uncertainty, and complexity.…”
Section: Review Of Relatedmentioning
confidence: 99%
“…Naïve Bayes -NB [59], [71], [76] 6 Random Forest -RF [71], [75], [86], [87] 7 Support Vector Machine -SVM [71], [73], [75], [76], [88], [89] 8…”
Section: Rq2: What Are the Most Commonly Used Ai Techniques And/or Al...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric analysis can be defined as a systematic, popular, and effective method that allows the analysis and inference of studies in the literature based on certain characteristics through a large-scale search using mathematical and statistical techniques [15][16][17]. There are several types of bibliometric analysis, including keyword analysis, content analysis, country analysis, citation analysis, publication year analysis, journal analysis, and author analysis [18].…”
Section: Definition and Scope Of Bibliometric Analysismentioning
confidence: 99%